The Effect of Yeast Dose and Fermentation Time on the Quality of Virgin Coconut Oil (VCO) - Delfrida Karlani Nahak; MM Endah Mulat Satmalawati; Hyldegardis Naisali (The University of Lampung, 2023)
Coconut are tropical plants and can be easily found in Indonesia. Virgin Coconut Oil (VCO) is one of the products produced from coconut beans. VCO is processed using fermentation techniques to maintain its quality and purity. This study aimed to determine the effect of yeast dosage and fermentation time on VCO yield, water content, and free fatty acids. Yeast dosage and fermentation time were the two treatment factors used in this study with a factorial Completely Randomized Design (CRD). To assess the impact of each treatment, the data was analyzed by using ANOVA with the significance level of 95%, followed using the Zeleny method analysis to find the best treatment condition. The oil found in this study was in compliance with SNI 7381:2008 and Asian Pacific Coconut Community (APCC) standards. The effect of yeast dose and fermentation period on oil yield, water content, and free fatty acid content in VCO was significant at α = 0.05. The results of the analysis showed that the best treatment condition was found at a yeast rate of 10 g and a fermentation time of 20 h. This treatment resulted about 15.67% oil yield with 0.2% moisture content and 0.2% free fatty acids. Keywords: Virgin coconut oil; yeast; time; yield; free fatty acid